Modeling and analysis of wastewater heat recovery system in Kuwait - Aldousari, Meshal R. E. E. M; Okasha, Mohamed Elsayed Aly Abd Elaziz; Faris, Waleed Fekry; Ghazaly, Nouby M. (TJPRC Pvt. Ltd., 2020)
Wastewater heat recovery become an important activity which could lead to the energy saving improvement and supports the carbon footprint reduction. Reducing a 1m3 cubic of wastewater temperature by 1 OC could recover around 1.2 kWh of heat. That is quite a significant amount of energy. The objective of this paper is to develop and optimize a numerical model on estimating the wastewater heat recovery of wastewater system at Jahra Governate in Kuwait. A map of the wastewater grid will be acquired in order to develop the network of a heat transfer model. Some points of interest will be located in order to simulate the implementation of the sewer heat exchanger and the heat pump model. The scenario of different type of heat exchangers and heat pumps model will be compared and optimized. The effect of the different installation of the heat recovery components to the process of the wastewater transportation is also should be considered. The main purpose of the wastewater system should not be disturbed. Final stage is the evaluation on the energy efficiency of the proposed heat recovery system.